Income and cash flow in some agricultural enterprises of Hajdu-Bihar county on the basis of data in 1997-98 - Rózsa, Attila (Acta Agraria Debreceniensis, 2001)
The income of agricultural enterprises varies greatly according to the type of agricultural production. The available data was classified and averaged on the basis of the form of association. Although the management of the examined enterprises ensured a profit, closer analysis of their cash flows reveals that, at least in some cases, expenses were not always coverable, despite income. In all forms of association major emphasis was put on improvement and support investments. It is highly probable that later on these investments will result in an increasing income level and profit. The situation is the most advantageous in the case of co-operatives, as the cash flow of the second examined year originated from regular activity could cover the cash flow of investments and financing. In the case of limited liability and shareholder companies the above is not true, but advantageous changes occur there too. Unfortunately, in most cases the role of loans is very important in the operation of the company. As far as favourable aspects are concerned it can be stated that credit repayment covered by the regular activity.